The checklists: A help or a hassle? - Andrés Concha-Torre; Yolanda Díaz Alonso; Sara Álvarez Blanco; Ana Vivanco Allende; Juan Mayordomo-Colunga; Bárbara Fernández Barrio (Elsevier, 2020)
Patient safety has become a central component of quality of care. One of the best known and most widely used security tools in all work settings is the checklists.The checklist is a tool that helps to not forget any step during the performance of a procedure, to do tasks with an established order, to control the fulfillment of a series of requirements or to collect data in a systematic way for its subsequent analysis. It is an aid to improve the efficiency of teamwork, promote communication, decrease variability, standardize care and improve patient safety.Main barriers to implementation are reviewed: staff attitudes, hierarchies, poor design, inadequate training, duplication with other work lists, work overload, cultural barriers, lack of replication or checklist closing time.Finally, its applications in Pediatrics are reviewed starting from the most widespread, the safety checklist of pediatric surgery, checklists in neonatal critical units, for safe delivery, for risk procedures, in pediatric intensive care and for pathology time-dependent emergent, e.g. pediatric trauma.It is necessary to highlight the role of leadership in the implantation of a checklist in any area of ​​Pediatrics. There must be one or more people from the team with the support of the Heads of Service and Managers who lead the training of the personnel, direct the implementation of the LV, evaluate the results, inform the rest of the team and can modify the processes depending on the problems found. Resumen: La seguridad de los pacientes se ha convertido en un componente central de la calidad asistencial. Una de las herramientas de seguridad más conocidas y extendidas en todos los ámbitos laborales son las listas de verificación (LV).Una LV es una herramienta que ayuda a no olvidar ningún paso durante la realización de un procedimiento, hacer tareas con un orden establecido, controlar el cumplimiento de una serie de requisitos o recoger datos de forma sistemática para su posterior análisis. Es una ayuda para mejorar la eficacia del trabajo en equipo, fomentar la comunicación, disminuir la variabilidad, estandarizar la atención y mejorar la seguridad de los pacientes.Se repasan las principales barreras para la implantación como las actitudes del personal, jerarquías, diseño deficiente, capacitación inadecuada, duplicación con otras listas de trabajo, sobrecarga de trabajo, barreras culturales, falta de replicación o tiempo de cierre de la LV.Finalmente se revisan sus aplicaciones en la edad pediátrica partiendo desde la más extendida, la LV de seguridad de la cirugía pediátrica, el parto y periodo neonatal (LV de unidades de críticos neonatales, LV para el parto seguro), para procedimientos de riesgo, para cuidados intensivos pediátricos y para la patología emergente tiempo-dependiente, por ejemplo, el trauma pediátrico.Es importante remarcar el papel del liderazgo en la implantación de una LV en cualquier área de trabajo de la Pediatría. Debe haber una o más personas del equipo con el apoyo de los Jefes de Servicio y Directivos que lideren la formación del personal, dirijan la implantación de la LV, evalúen los resultados, informen al resto del equipo y puedan modificar los procesos en función de los problemas encontrados.